Predicting mechanical properties of polyvinylidene fluoride/carbon nanotube composites by molecular simulation. (17th November 2017) - Chen, Hui-Lung; Su, Chia-Hao; Ju, Shin-Pon; Chen, Hsing-Yin; Lin, Jenn-Sen; Hsieh, Jin-Yuan; Yang, Po-Yu; Lin, Chen-Yun
Abstract: Pristine polyvinylidene fluoride (PVDF) and its CNT composites (PVDF/CNT) at three CNT weight fractions, 8 wt%, 16 wt% and 24 wt%, were used to investigate the influence of CNT fraction on the mechanical properties of PVDF. Molecular dynamics (MD) simulation was utilized to predict the mechanical properties of PVDF/CNT composites. The tensile stress–strain profiles indicate that the Young's modulus and tensile strength of pristine PVDF can be significantly improved by the embedded CNTs. However, these CNTs induce stress concentration within the composites, resulting in increased brittleness and a fracture at lower strains. By taking advantage of this molecular simulation procedure, fast comparable predictive properties of PVDF/CNT composites could be performed, with the simulation results providing atomistic-level insights into this new pathway to reduce the cost and research time in related experiments.